Metal phthalocyanine compound doped MXene material for positive electrode of lithium-sulfur battery and preparation method of metal phthalocyanine compound doped MXene material
By using metal phthalocyanine compound doping MXene material in the positive electrode of lithium sulfur battery, the problems of low conductivity and shuttle effect of lithium sulfur battery positive electrode are solved, and the electrochemical performance and cycle life are significantly improved.
Patent Information
- Application Number
- CN202411601730.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-11
AI Technical Summary
Problems such as low positive conductivity, lithium dendrites growth and shuttle effects of lithium sulfur batteries affect their electrochemical performance and cycle life.
The MXene material was doped with metal phthalocyanine compound, and a single layer MXene colloidal solution was prepared by etching method, and the metal phthalocyanine compound and carbon nanotube were added. The mixed solution was prepared by magnetic stirring and ultrasonication. After freeze-drying, the black powder MX-NiPC catalytic material was calcined at high temperature.
The electrochemical performance and cycle life of lithium-sulfur batteries have been improved. The release specific capacity of Li2S/MX-NiPC in the first round at 0.1C is as high as 872mAh/g, which is 40% higher than Li2S/MX, and the capacity after 100 cycles at 1C is 35% higher than Li2S/MX.
Smart Images

Figure CN119581512A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy material preparation, and in particular to a metal phthalocyanine compound-doped MXene material for a lithium-sulfur battery positive electrode and a preparation method thereof. Background Art
[0002] Lithium-sulfur batteries have the advantages of high theoretical energy density, high theoretical specific capacity, low price, and environmental friendliness, and have become the next generation of energy storage systems that researchers focus on. Lithium-sulfur batteries have obvious advantages, but their inherent disadvantages cannot be ignored, including low positive electrode conductivity, lithium dendrite growth, and shuttle effect, which are problems that lithium-sulfur batteries must overcome in order to be commercialized.
[0003] For example, patent publication number CN108232115B discloses a lithium-sulfur battery positive electrode material and a preparation method thereof, a lithium-sulfur battery and a lithium-sulfur battery. The provided lithium-sulfur battery positive electrode material is a composite material formed by cobalt salt (magnesium cobaltate, nickel cobaltate, copper cobaltate and zinc cobaltate) and sulfur, and the content of sulfur is 60-90wt%. The provided cobalt salt has a strong adsorption effect on polysulfide, can effectively inhibit the dissolution of lithium polysulfide in ether electrolyte, slow down the shuttle effect during battery charging and discharging, reduce the capacity decay of lithium-sulfur battery, and improve battery life. The provided lithium-sulfur battery has an initial discharge capacity of 955mAh / g (calculated according to the composite material) at a current of 0.1C, a capacity of 722mAh / g after 100 cycles, and a capacity retention rate of 75.6%.
[0004] MAX phase is a type of phase with chemical formula M n+1 AX nA ternary layered compound, where M represents a transition metal element, including Sc, Ti, Zr, Hf, V, Nb, Ta, Cr and Mo; A represents a III A or IVA group element; X represents C or N; and the value of n is 1, 2 and 3. The structural characteristics of the MAX phase are that the M atoms and the A atomic layers are arranged alternately to form a nearly close-packed hexagonal layered structure, and the X atoms fill the octahedral interstitial sites. The MA bond has the characteristics of a metallic bond, and the bond energy is weaker than that of the MX bond. Therefore, the A atomic layer in the MAX phase is easily etched by HF solution. MXene materials are mainly prepared by selectively etching away the A atomic layer in the MAX phase. In recent years, with the continuous exploration of the MXenes material family, researchers have found that it has unique structural and surface chemical properties, metallic conductivity, excellent hydrophilicity and good mechanical stability, showing application prospects in many fields, such as energy storage, electromagnetic interference shielding, electrocatalytic hydrogen evolution, piezoresistive sensors and membrane separation. With the advancement of research, more and more MXene materials are being used in lithium-sulfur batteries. In addition to the lithium-sulfur battery positive electrode materials and their preparation methods and lithium-sulfur batteries disclosed above, the existing research on the application of MXene materials in lithium-sulfur batteries mostly focuses on structural design and chemical adsorption. There is still room for improvement in the catalytic conversion of polysulfides by MXene-based positive electrode materials. Summary of the invention
[0005] The purpose of the present application is to provide a metal phthalocyanine compound doped MXene material for the positive electrode of a lithium-sulfur battery and a preparation method thereof to solve the problems raised in the above background technology.
[0006] To achieve the above-mentioned purpose, the present application provides the following technical solution: a method for preparing a metal phthalocyanine compound-doped MXene material for a lithium-sulfur battery positive electrode, comprising the following steps:
[0007] (1) Prepare a single-layer MXene colloidal solution by etching method;
[0008] (2) adding an ethanol solution of a metal phthalocyanine compound and an aqueous solution of carbon nanotubes to a monolayer MXene colloidal solution, and preparing a mixed solution by magnetic stirring and ultrasound;
[0009] (3) The mixed solution is freeze-dried and then calcined at high temperature to obtain a black powder MX-NiPC catalytic material.
[0010] As a further supplement to the present solution, the etching method adopts one of a hydrofluoric acid etching method, a hydrochloric acid + lithium fluoride etching method and a molten salt etching method.
[0011] As a further supplement to this scheme, in step (1), the specific method for preparing a single-layer MXene colloidal solution using the HCl+lithium fluoride etching method is as follows:
[0012] 1) Add lithium fluoride powder to concentrated HCl under stirring at room temperature, and slowly add MAX phase precursor material after lithium fluoride is completely dissolved;
[0013] 2) The solution obtained in step 1) was stirred in an oil bath at 35-45° C. for 22-26 h, then centrifuged and washed with water until the pH value was 7, ultrasonicated in an ice bath for 0.5-1 h, and then centrifuged for 10 min, and the upper suspension was collected to obtain a monolayer MXene colloidal solution.
[0014] As a further supplement to this scheme, in step 1), the concentration of concentrated HCl is 8-12 M, the concentration of lithium fluoride in concentrated HCl is (0.04-0.1) g / mL, and the mass ratio of lithium fluoride to MAX phase is (0.75-3.5):1.
[0015] As a further supplement to this solution, the MAX phase precursor material is one or more of Ti3AlC2, Cr2AlC, V2AlC, Mo2TiAlC2, Ta2AlC, and Ta4AlC3.
[0016] As a further supplement to this scheme, in the step 2), the rotation speed of the centrifugal water washing is 3000-4500 r / min, the rotation speed of the centrifugal washing after ultrasound is 4000-6000 r / min, and the concentration of the single-layer MXene colloid solution is 5-10 mg / mL.
[0017] As a further supplement to this scheme, the concentration of the carbon nanotube aqueous solution in step (2) is 40-60 mg / mL, and the volume ratio of the carbon nanotube aqueous solution to the monolayer MXene colloid solution is 1:(5-20);
[0018] The metal phthalocyanine compound in step (2) is one or more of copper phthalocyanine, nickel phthalocyanine, zinc phthalocyanine, cobalt phthalocyanine, and iron phthalocyanine, and the concentration of the ethanol solution of the metal phthalocyanine compound is 0.5-4 mg / mL.
[0019] As a further supplement to this solution, when treating the mixed solution in step (2), the ultrasonic time is 0.5-1h.
[0020] As a further supplement to this scheme, during the freeze-drying in step (3), the freezing time is 12-24 hours and the drying time is 36-48 hours;
[0021] The calcination temperature in step (3) is 300-400° C., the heating rate is 1-5° C. / min, the calcination time is 2-4 h, and the atmosphere is argon or nitrogen.
[0022] A metal phthalocyanine compound-doped MXene material for a lithium-sulfur battery positive electrode, wherein the metal phthalocyanine compound-doped MXene material is prepared according to the above-mentioned method for preparing the metal phthalocyanine compound-doped MXene material for a lithium-sulfur battery positive electrode.
[0023] In summary, the technical effects and advantages of the present invention are as follows:
[0024] 1. The present invention adopts freeze-drying method + annealing method to synthesize metal phthalocyanine compound doped MXene material. MXene provides Ti-chemical adsorption group, and metal phthalocyanine compound provides active catalytic conversion group. The synergistic effect of the two can play an adsorption-catalytic conversion role, thereby improving the utilization rate of active substances and inhibiting the shuttle effect. Finally, the first cycle release capacity of Li2S / MX-NiPC at 0.1C is as high as 872mAh / g, which is 40% higher than that of Li2S / MX. The capacity after 100 cycles at 1C is 35% higher than that of Li2S / MX, which greatly improves the electrochemical performance and cycle life of lithium-sulfur batteries.
[0025] 2. In the present invention, the preparation method of the present invention is scientific, reasonable, easy to implement and low-cost. The obtained metal phthalocyanine compound-doped MXene material has the advantages of simple synthesis, easy adjustment of coordination composition, and can effectively reduce shuttling, improve charge and discharge capacity, and extend the cycle life of lithium sulfide-based lithium-sulfur batteries, providing an important reference for the next generation of high-performance lithium sulfide-based lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0027] Figure 1 This is the SEM spectrum of the prepared metal phthalocyanine compound doped MXene material;
[0028] Figure 2 This is the XRD pattern of the prepared metal phthalocyanine compound doped MXene material;
[0029] Figure 3 Comparison of charge and discharge of prepared Li2S / MX and Li2S / MX-NiPC at a current rate of 0.1C;
[0030] Figure 4 (a) Rate performance comparison of Li2S / MX-NiPC and Li2S / MX, (b) Cycling performance comparison of Li2S / MX-NiPC and Li2S / MX at 1C;
[0031] Figure 5 This is a CV comparison chart of Li2S / MX-NiPC and Li2S / MX. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] 1. Preparation of MX-NiPC
[0035] (1) Add 40 mL of HCl to a polytetrafluoroethylene beaker, and slowly add 3.2 g of lithium fluoride while stirring the HCl solution to completely dissolve it. Weigh 2.0 g of MAX phase (Ti3AlC2) and slowly add it to the above solution, stirring and heating for 24 h at a temperature of 40°C.
[0036] (2) Centrifuge the etched solution for 6 minutes at a centrifugal speed of 3500 r / min. Pour out the supernatant, shake well and centrifuge, and repeat the above steps 6 times until the pH of the supernatant is 6-7.
[0037] (3) Add distilled water and shake to obtain a black solution. Combine the solutions in the four test tubes into two test tubes, pass inert gas (argon) for 5 min to remove oxygen from the solution, and perform ultrasonic treatment twice, each for 20 min.
[0038] (4) The sonicated solution was centrifuged for 10 min at a speed of 6000 r / min. The solutions in the two test tubes were poured into two beakers (A and B) respectively, and the unreacted MAX solids at the bottom were directly discarded. 5 mL of carbon nanotube aqueous solution was added to beaker A and stirred for 30 min. 5 mL of carbon nanotube aqueous solution was added to beaker B, 0.05 g of nickel phthalocyanine (NiPc) was weighed and added to 5 mL of anhydrous ethanol and stirred to obtain a nickel phthalocyanine ethanol solution, and the nickel phthalocyanine ethanol solution was added to beaker B and stirred for 30 min.
[0039] (5) Solutions A and B were ultrasonicated for 30 min, frozen for 24 h, freeze-dried for 48 h, and then annealed in a tube furnace at 400 °C in an argon atmosphere for 2 h to obtain nickel phthalocyanine-doped MXene material (MX-NiPC) at a heating rate of 2 °C / min.
[0040] Figure 1This is the SEM image of MX-NiPC obtained in Example 1. The three-dimensional structure of MXene and the distribution of NiPC particles can be observed in the figure. Its three-dimensional structure helps to accommodate active substances. The Ti contained in MXene can provide Ti-S bonds to form effective adsorption of polysulfides, and the catalytic center provided by NiPC can quickly convert polysulfides to avoid excessive polysulfide concentrations leading to the appearance of dead sulfur or shuttle effect, which in turn leads to permanent loss of active substances.
[0041] Figure 2 is the XRD pattern of MX-NiPC obtained in Example 1. Figure 2 It can be seen from (a) that the peak of the raw material MAX phase used corresponds to the peak of the PDF standard card of Ti3AlC2 and there is no obvious impurity peak, which shows that the MAX phase used this time is of extremely high purity. Among them, the diffraction peaks at 9.6°, 34.1°, 38.9°, 42.0°, and 60.2° correspond to the (002), (101), (104), and (109) crystal planes of Ti3AlC2, respectively. The strongest diffraction peak (38.9°) in the XRD spectrum of MXene after etching disappears, indicating that the Al layer in the MAX phase is completely stripped off after etching, and the diffraction peak at 9.6° shifts to the left to 7.5°. According to the Bragg equation, it is inferred that the interplanar spacing increases. Further analysis shows that the Ti-Al bond of the MAX phase is destroyed during the acid etching process, and the Al layer is etched away, which increases the interplanar spacing, indicating that the single-layer MXene is successfully synthesized.
[0042] X-ray diffraction tests were performed on MXene and MX-NiPC obtained by different doping. The results are as follows: Figure 2 As shown in (b), both have characteristic peaks at 7.5°, which is consistent with undoped MXene. Since NiPC is slightly doped, no obvious diffraction peaks can be seen in the XRD pattern.
[0043] Example 2
[0044] 1. Preparation of MX-NiPC
[0045] (1) Add 40 mL of HCl to a polytetrafluoroethylene beaker, and slowly add 3.2 g of lithium fluoride while stirring the HCl solution to completely dissolve it. Weigh 2.0 g of MAX phase (Ti3AlC2) and slowly add it to the above solution, stirring and heating for 24 h at a temperature of 40°C.
[0046] (2) Centrifuge the etched solution for 6 minutes at a centrifugal speed of 3500 r / min. Pour out the supernatant, add distilled water to 35 mL, shake well and centrifuge. Repeat the above steps 6 times until the pH of the supernatant is 6-7.
[0047] (3) Add distilled water and shake to obtain a black solution. Combine the solutions in the four test tubes into two test tubes, pass inert gas (argon) for 5 min to remove oxygen from the solution, and perform ultrasonic treatment twice, each for 20 min.
[0048] (4) The sonicated solution was centrifuged for 10 min at a speed of 6000 r / min. The solutions in the two test tubes were poured into two beakers (A and B) respectively, and the unreacted MAX solids at the bottom were directly discarded. 5 mL of carbon nanotube aqueous solution was added to beaker A and stirred for 30 min. 5 mL of carbon nanotube aqueous solution was added to beaker B, 0.1 g of nickel phthalocyanine (NiPc) was weighed and added to 5 mL of anhydrous ethanol and stirred to obtain a cobalt phthalocyanine ethanol solution, and the nickel phthalocyanine ethanol solution was added to beaker B and stirred for 30 min.
[0049] (5) Solutions A and B were ultrasonicated for 30 min, frozen for 24 h, freeze-dried for 48 h, and then annealed in a tube furnace at 350 °C in a nitrogen atmosphere for 2 h to obtain nickel phthalocyanine-doped MXene material (MX-NiPC) at a heating rate of 1 °C / min.
[0050] 2. Preparation of electrodes and batteries
[0051] (1) MX-NiPC, Li2S, conductive carbon black, and a binder are ground and mixed in a ratio of 3:5:1:1, and N-methylpyrrolidone (NMP) is added and stirred for 4-8 hours to form a uniform slurry. The slurry is coated, dried, and cut into pieces to obtain a Li2S / MX-NiPC positive electrode sheet.
[0052] (2) Li2S / MX-NiPC positive electrode sheet, Celgard 2400 separator, lithium sheet, positive and negative electrode shells were assembled into a Li-S battery, and electrochemical testing was performed after standing for 8-12 hours.
[0053] Figure 3The first charge and discharge activation curves of Li2S / MX and Li2S / MX-NiPC at 0.1C in Example 2 are shown. Since lithium sulfide is a product of complete lithiation of elemental sulfur and has poor conductivity, it needs to be charged to 3.6V to overcome its activation barrier during the first charge process. In the subsequent charge and discharge process, since there is already a trace amount of lithium polysulfide in the system that can undergo a disproportionation reaction with lithium sulfide, the conversion reaction can be completed without overpotential. As can be seen from the figure, the activation barrier of Li2S / MX-NiPC is about 2.75V, while the activation barrier of Li2S / MX is as high as 3.6V due to its lack of active centers for catalytic conversion. This shows that the addition of NiPC has a catalytic effect on the conversion reaction of Li2S to Li2S8. The reduction of the first charge voltage is of great significance to the protection of the electrolyte, which can prevent the decomposition of the electrolyte under high voltage. On the other hand, Li2S / MX-NiPC releases an initial specific capacity of 847mAh / g, while Li2S / MX only has an initial discharge specific capacity of 622mAh / g. Both have a long discharge platform at 2.12V, corresponding to the conversion reaction of liquid polysulfide. The first cycle charge and discharge test results show that Li2S / MX-NiPC has a lower activation voltage and a higher discharge specific capacity, which indicates that the addition of NiPC accelerates the conversion reaction and improves the utilization rate of active materials.
[0054] Figure 4 (a) is a comparison chart of the discharge specific capacities of Li2S / MX and Li2S / MX-NiPC at different rates. It can be seen from the figure that the discharge specific capacities of Li2S / MX and Li2S / MX-NiPC at current rates of 0.1C, 0.2C, 0.5C, 1C, and 2C are 745.8 / 520.4, 667.8 / 475.3, 593.5 / 443.7, 528.8 / 414.6, and 465.7 / 348.7 mAh / g, respectively. When the current rate is restored to 0.1C, the discharge specific capacities of Li2S / MX and Li2S / MX-NiPC are 655.2 mAh / g and 482 mAh / g, respectively, and the Li2S / MX-NiPC cathode maintains a high discharge specific capacity. Figure 4 (b) is a comparison of the cycling performance of Li2S / MX-NiPC and Li2S / MX at a current rate of 1C. It can be seen that the first discharge specific capacities of Li2S / MX-NiPC and Li2S / MX are 522.8mAh / g and 420.6mAh / g, respectively. After 100 cycles, the discharge specific capacities drop to 400.8mAh / g and 289.6mAh / g, respectively, and the capacity retention rates are 76.6% and 68.8%, respectively. The specific capacity and cycling stability of the Li2S / MX-NiPC cathode are both better than those of Li2S / MX.
[0055] Comparative Example 1
[0056] Compared with Experimental Example 1, the rest of the experimental process of Comparative Example 1 remains unchanged, except that the addition of the metal phthalocyanine compound is removed during the preparation process to obtain MX. Due to the lack of catalytic centers, the final Li2S / MX first cycle release capacity at 0.1C is only 621mAh / g, which is 28.8% lower than that of Li2S / MX-NiPC in Experimental Example 2, and the capacity after 100 cycles at 1C is 28.3% lower than that of Li2S / MX-NiPC in Experimental Example 2.
[0057] Figure 5 The cyclic voltammetry (CV) curves of Li2S / MX-NiPC and Li2S / MX are shown in Figure 2. The positions of the two reduction peaks and one oxidation peak of the two are almost the same, but the current of Li2S / MX-NiPC is higher than that of Li2S / MX. Analysis shows that the areas of the reduction peak and oxidation peak of Li2S / MX-NiPC are slightly higher than those of Li2S / MX, so the utilization rate of active substances of Li2S / MX-NiPC is higher than that of Li2S / MX. From the CV test, it can be seen that at different scan speeds, Li2S / MX-NiPC maintains a better peak structure, and the voltage window of the electrochemical reaction is more concentrated, indicating that the electrochemical reaction rate is faster. Li2S / MX-NiPC has a higher reaction voltage in the reduction reaction, indicating that less energy is required for the reduction reaction, which confirms the rapid catalytic conversion ability of Li2S / MX-NiPC.
[0058] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a metal phthalocyanine compound-doped MXene material for a lithium-sulfur battery positive electrode, characterized in that: The following steps are involved: (1) Preparation of single-layer MXene colloidal solution; (2) Adding a metal phthalocyanine compound ethanol solution and CNTs to a single-layer MXene colloidal solution, and preparing a mixed solution by magnetic stirring and ultrasound; (3) The mixed solution is freeze-dried and then calcined at high temperature to obtain a black powder MX-NiPC catalytic material. (4) Prepare Li2S / MX-NiPC positive electrode material and assemble it into a lithium-sulfur battery.
2. The method for preparing a metal phthalocyanine compound-doped MXene material for a lithium-sulfur battery positive electrode according to claim 1, characterized in that: The etching method adopts one of a hydrofluoric acid etching method, a hydrochloric acid + lithium fluoride etching method and a molten salt etching method.
3. The method for preparing a metal phthalocyanine compound-doped MXene material for a lithium-sulfur battery positive electrode according to claim 1, characterized in that: The raw material MAX phase includes but is not limited to one or more of Ti3AlC2, Cr2AlC, V2AlC, Mo2TiAlC2, Ta2AlC, and Ta4AlC3.
4. The method for preparing a metal phthalocyanine compound-doped MXene material for a lithium-sulfur battery positive electrode according to claim 3, characterized in that: The metal phthalocyanine compound includes but is not limited to one or more of nickel phthalocyanine (NiPc), cobalt phthalocyanine (CoPc), copper phthalocyanine (CuPc), iron phthalocyanine (FePc), manganese phthalocyanine (MnPc), and zinc phthalocyanine (ZnPc). The preferred concentration of the metal phthalocyanine ethanol solution is 0.5-4 mg / mL.
5. The method for preparing a metal phthalocyanine compound-doped MXene material for a lithium-sulfur battery positive electrode according to claim 4, characterized in that: The concentration of concentrated hydrochloric acid is 8-12 mol / L, the concentration of LiF in concentrated HCl is (0.04-0.1) g / mL. The mass ratio of LiF to MAX phase is (0.75-3.5):
1.
6. The method for preparing a MXene colloidal solution according to claim 1, characterized in that: The concentration of the monolayer MXene colloidal solution is 5-10 mg / mL.
7. The method for preparing a metal phthalocyanine compound-doped MXene material for a lithium-sulfur battery positive electrode according to claim 3, characterized in that: In the step 2), the rotation speed of the centrifugal water washing is 3000-4500 r / min, the rotation speed of the centrifugal washing after ultrasound is 4000-6000 r / min, and the concentration of the single-layer MXene colloidal solution is 5-10 mg / mL.
8. The method for preparing a metal phthalocyanine compound-doped MXene material for a lithium-sulfur battery positive electrode according to claim 1, characterized in that: The concentration of the carbon nanotube aqueous solution in step (2) is 10-80 mg / mL, and the volume ratio of the carbon nanotube aqueous solution to the monolayer MXene colloid solution is 1:(5-20); 9. The method for preparing a metal phthalocyanine compound-doped MXene material for a lithium-sulfur battery positive electrode according to claim 1, characterized in that: When the mixed solution is treated in step (2), the ultrasonic time is 0.5-1 h.
10. The method for preparing a metal phthalocyanine compound-doped MXene material for a lithium-sulfur battery positive electrode according to claim 1, characterized in that: During freeze drying in step (3), the freezing time is 12-24 h and the drying time is 36-48 h; The calcination temperature in step (3) is 300-400°C, the heating rate is 1-5°C / min, the calcination time is 2-4 h, and the atmosphere is argon or nitrogen.
11. A metal phthalocyanine compound doped MXene material for lithium-sulfur battery positive electrode, characterized in that: The metal phthalocyanine compound-doped MXene material is prepared according to the method for preparing a metal phthalocyanine compound-doped MXene material for a lithium-sulfur battery positive electrode as claimed in claim 1.
Citation Information
Patent Citations
Nitrogen-nickel co-doped MXene in-situ derived titanium dioxide interface structure material and preparation method thereof
CN118304917A
Three-dimensional multifunctional TiN-MXene-Co-CNTs heterostructure material as well as preparation method and application thereof
CN118398814A
KR20220037862A